Avaliação das Flagelinas Leptospirais como adjuvantes para o desenvolvimento de uma vacina subunitária contra a leptospirose - Monaris, D.; Souza, G. O.; Vasconcellos, S. A.; Ferreira, L. C. S.; Abreu, P. A. E. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is a zoonosis of global importance caused by pathogenic leptospires that colonize the renal tubules of wild and domestic animals. Commercial bacterines are being used, but they canpromote protection only against the serovar included in the preparation and they I can induce a shortterm immunity. The LigAC is able to induce immunoprotection against leptospirosis. However, immunization with LigAC did not confer sterilizing immunity. Flagellins have been considered a promising adjuvant for vaccine development. Leptospires have two periplasmic flagella that are formed by two classes of proteins (FlaA and FlaB); only FlaB proteins show homology with important regions that elicit TLR5-dependent responses.